Development of a method for determining the mass fraction of cocoa products in confectionery by the content of alkaloids - N. B. Kondratev; O. S. Rudenko; M. V. Osipov; I. A. Belova (Пищевые системы)
The presence of methylxanthine alkaloids such as caffeine, theobromine and theophylline is characteristic of cocoa bean processing products, but theobromine is not contained in other types of raw materials. Therefore, the theobromine content can be used as an indicator of the content of cocoa products. Cocoa products are used in various types of confectionery products to improve the taste and aroma; however, there are no methods to determine the content of cocoa products in confectionery products that do not belong to the chocolate group. Cocoa bean processing products such as cocoa powder, cocoa mass and sugar confectionery products, including chocolate, confectionery bars and wafer fillings made with their use, were objects of the study. Theobromine and caffeine were determined using the capillary electrophoresis method after acid hydrolysis of samples. The theobromine content in cocoa beans, cocoa powder and cocoa mass was determined. Based on these data, the theobromine content was calculated in terms of dry fat-free solids of cocoa of 1560 mg/100 g and a formula was proposed for calculating the mass fraction of dry fat-free solids of cocoa. The developed method with calculated metrological indicators allows measuring the mass fraction of dry fat-free solids of cocoa in sugar confectionery products made from cocoa bean processing products. The proposed approach can be used as an effective express method for studying the composition of multicomponent sugar confectionery products to assess their quality and determine the amount dry fat-free solids of cocoa, which is the most important identification criterion for the content of cocoa bean processing products.